Financial statements analysis: A case study of Southerner Industries Sdn. Bhd. / Hairul Anuar Samsudin - Samsudin Ida Ingko, Hairul Anuar; Ingko, Ida; Ali, Sorayahyati (2012)
The aim of this paper is to analyze the audited financial statements of Southerner Industries Sdn Bhd using financial ratios analysis to identify potential problems areas of the company. Horizontal analysis or trend analysis and cash flows analysis would also be done to support the findings of the financial ratios analysis. Based on the problem identified, structured interviews were conducted to further clarify on problem areas identified from the financial ratio analysis, horizontal analysis or trend analysis and cash flows analysis. A SWOT analysis will also be constructed based on the results and findings of financial ratios analysis, horizontal analysis, cash flows analysis and the structured interviews. Recommendations would also be made to the management of Southerner Industries Sdn Bhd, based on the SWOT analysis, which incorporates the results and findings of the financial ratios analysis, horizontal analysis, cash flows analysis and also the structured interviews. It is hopes that the findings and the recommendations made would help Southerner Industries Sdn Bhd to improve its financial performance and also encourage more in-depth research to be done based on the findings of this study.